A new species of Wallacea Baly (Coleoptera: Chrysomelidae: Cassidinae: Bothryonopini) infesting coconut palm in the Indian Ocean Islands of Andaman & Nicobar - Prathapan, K. D.; Shameem, K. M. (Zootaxa, 2017)
Wallacea jarawa n. sp. infesting coconut palm (Cocos nucifera L., Arecaceae) in the Indian Ocean Islands of Andaman & Nicobar is described and illustrated. The structure of the endophallic sclerites is illustrated and used in species recognition. Borassus flabellifer L. (Arecaceae) and an unidentified rattan cane (? Calamus sp., Arecaceae) are reported as additional host plants.